Model Pembelajaran Agata-Stick Untuk Meningkatkan Partisipasi Dan Ketertarikan Belajar Pendidikan Kewarganegaraan Pada Siswa Kelas Vii-F Smp Muhammadiyah 7 Surakarta Tahun Pelajaran 2015/2016 - Muharam, Latif; , Dr. Ahmad Muhibbin M.Si (2016)
This research aims to increase participation and interest of the students in learning Civic Education in class VII-F of SMP Muhammadiyah 7 Surakarta in the academic year 2015/2016 through the application of learning models AGATA-STICK which collaborate the strategies of Answers Gallery and Talking Stick. The kind of research is Research and Development (R&D). The techniques of collecting data use observation, interviews and questionnaires method. The procedures in this research include planning, trial's implementation, evaluation, improvement and refinement of the model. Instrument's validity uses product moment crude rate, while reliability uses split half's technique which split data of odd number' score and even number' score. The analysis of this research uses flow model and validity uses triangulation by sources. This research conducted in two trials models. Expected by using AGATA-STICK's model is able to increase participation and interest of the students in learning Civic Education in class VII-F of SMP Muhammadiyah 7 Surakarta academic year 2015/2016. The results show the score of students' participation in the trial of first model are 36.89 or 70.94%. After the trial of second model, the score increases into 44.21 or 85.01%. The other result show the score of students' interest in the trial of the first model are 31.89 or 66.85% and after the trial of the second model, the score increases into 36.42 or 75.87%. Based on that result, it already shows an increase significantly. It means or it can be concluded that the application of learning model AGATA-STICK is able to increase participation and interest of the students in class VII-F of SMP Muhammadiyah 7 Surakarta in learning Civic education.